P196 Work-related asthma in stainless steel welders, irritant or allergy?. (11th November 2022) - Moore, VC; Huntley, CC; Robertson, AS; Walters, GI
Abstract : Background: Work-related asthma in welders is often thought to be irritant rather than allergic, limiting the availability of surveillance, assisted retraining and compensation. Excess inflammatory gene activation is a feature of asthma in stainless-steel welders compared with isocyanate asthma. We have investigated a cohort of stainless-steel welders with work-related asthma to see if they best fit irritant or allergic endotypes. Methods: Sequential stainless-steel welders with work-related asthma were included. The timing of the start and recovery of falls of Peak Expiratory Flow (PEF) were identified from Oasys analysis of 2-hourly measurements at work and home recorded for 4 weeks. Non-specific bronchial hyperresponsiveness (NSBR), atopy, eosinophilia and FeNO were measured at clinic visits while exposed. The irritant endotype was defined as either pre-existing asthma, or latency from first exposure <6 months or increased NSBR and the start of PEF decline <2 hours after starting work or the start of recovery <2 hours after leaving work ( figure 1 ). Results: Twenty-five welders showed changes in PEF confirming work-related asthma. One had pre-existing asthma, two had latencies from first exposure to first symptom <6 months and 3 had NSBR. A possible irritant endotype was present in 4/25. Peripheral eosinophilia and raised FeNO were uncommon. Specific inhalation testing with chromates showed a dual reaction in the only worker tested, with no response to welding mild steel or to potassium chloride adjusted to the same acid pH as the chromate solution, confirming specific chromate sensitisation in this welder. Conclusion: The endotype is incompatible with a purely irritant mechanism in 21/25 and has non-Th2 characteristics. Stainless-steel welders with work-related asthma should be managed as occupational asthma with hypersensitivity.